2022
DOI: 10.21608/ejhc.2022.228203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mothers' Heartbeats Combined with Swaddling Technique on Orogastric Tube Insertion Pain among Preterm Neonates

Abstract: Preterm neonates experience pain with several procedures within the Neonatal Intensive Care Units (NICUs). Significant evidences prove that controlling the neonates' pain is helpful in improving physiological, hormonal, and behavioral outcomes. Therefore, it is reasonable to manage preterm neonates' pain by integrating innovative non-pharmacological pain measures that will help those neonates to handle the stressful situations. Aim: The aim of this study was to determine the effect of mothers' heartbeats combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…As regards gender of the studied premature neonates, the present study showed that, less than three quarters of premature neonates in study group were females. This finding was in disagreement with (Radwan et al, 2022) who conduct study about "Effect of Mothers' Heartbeats and Swaddling Technique on Orogastric Tube Insertion Pain between Preterm Neonates" and reported that more than two thirds (66%) of Preterm Neonates in the study groups were males. The finding of the present study indicated that less than two thirds of premature neonates in the control group were born by caesarean section.…”
Section: Discussioncontrasting
confidence: 58%
“…As regards gender of the studied premature neonates, the present study showed that, less than three quarters of premature neonates in study group were females. This finding was in disagreement with (Radwan et al, 2022) who conduct study about "Effect of Mothers' Heartbeats and Swaddling Technique on Orogastric Tube Insertion Pain between Preterm Neonates" and reported that more than two thirds (66%) of Preterm Neonates in the study groups were males. The finding of the present study indicated that less than two thirds of premature neonates in the control group were born by caesarean section.…”
Section: Discussioncontrasting
confidence: 58%